Could Conservatism Reduces Earning Management Practice in IPO During the Current Covid-19 Pandemic? - Adhi, Dimas Hermawan Novi; Agusta, Stiven (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
The research examines the market reaction to the information prepared by two different accounting standards during the covid-19 pandemic, and the role of Conservatism in reducing the earning management practice in the initial public offerings (IPO). The response considers the rationality level, the avoidance risk, and accounting standards' role in preparing the information. An event study of IPO is conducted on the various primary market in the U.S., Europe, and Asia. Our conclusions are twofold. First, the market reacts quickly to the stated information, where the accounting standards influence the reaction level. Second, during the covid-19 pandemic, earnings management plays a role in increasing the market reaction intensity. At the same time, we have not found conservatism's role in reducing the earning management activity.